Finding the best fit for direct and indirect causation: a typological study - Levshina, Natalia (Lingua Posnaniensis, 2016)
The contrast between direct and indirect causation is the most widely discussed semantic distinction in the literature on causative constructions. This distinction has been claimed to correlate with a number of formal parameters, such as formal distance, productivity and length, which are linked to different functional and diachronic explanations based on the principles of iconicity and economy. The present study tests these claims on a typologically representative sample of languages from 46 diverse families, examining four formal variables and their association with (in)directness of causation. According to the data, formal length displays the most pervasive association with the semantic distinction in question, which supports the economy-based explanation. In addition, the relative prominence of the other formal parameters depends on the type of causatives and their stage of grammaticalization.